Uncertainties in nuclear matrix elements for neutrinoless double-beta decay. (5th February 2015) - Engel, Jonathan
Abstract: I briefly review calculations of the matrix elements governing neutrinoless double-beta decay, focusing on attempts to assign uncertainties. At present, systematic error dominates statistical error and assigning uncertainty is difficult. For some purposes, however, statistical assessment of uncertainty is profitable and, after describing the nuclear models in which matrix elements are commonly calculated, I highlight some statistical uncertainty analysis within the quasiparticle random-phase approximation. I also propose, in broad terms, strategies for reducing both systematic and statistical error.